Prevention of CSF leakage after endoscopic endonasal approach and effects of collaborative work - Ahmet Ozak; Cem Celal Aslan (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2020)
Endoscopic Endonasal Approach (EEA) has been used frequently in recent years, especially for the sellar pathologies. Although there is an increase in extent of tumor resection rates, the rates of CSF leakage appear to be high in patients undergoing EEA surgery. The use of pediculed nasoseptal flaps is gradually increasing for the prevention of rinorrheae. In pathologies requiring an extended approach such as extensive skull base tumors, ENT surgeon and neurosugeon collaborative works are considerable. In this way, both the exposure required for surgery can be achieved and postoperative nasal complications can be minimized by ensuring the protection of sinonasal structures.